G470 Early medical treatment of gender dysphoria: baseline characteristics of a uk cohort beginning early intervention. (27th April 2015) - Gunn, HM; Goedhart, C; Butler, G; Khadr, SN; Carmichael, PA; Viner, RM
Abstract : Aims: To describe characteristics of patients referred early (<16 yrs) medical treatment for gender dysphoria (GD). GD is a rare condition in which individuals experience clinically significant distress due to incongruence between their psychological perception of, and their natally assigned, sex. Methods: We collected data prospectively on all patients referred from May 2010––July 2014 for early pubertal suppression using gonadotropin – releasing hormone analogue (GnRHa) therapy. Results: 61 young people (34 natal males; 55.7%) were referred for early intervention to the national GD service endocrine liaison clinic at mean age of 13.1 years (range 9.8–15.3). All patients had a karyotype consistent with their natal sex. More natal males were in early puberty (32.4% Tanner 1/2; n = 11) than natal females (11.1% Tanner 1/2; n = 3). Baseline endocrinology and physical examination were normal for natal sex in all patients. All females who had standard synacthen tests to exclude adrenal dysfunction (77.8%; n = 21) had normal cortisol and 17OHP. 38.2% (n = 13) males had low bone mineral density compared with 11.1% of females (n = 3). 50 patients (81.9%) elected to receive GnRHa following full explanation and informed consent at Tanner stage 3, following international guidelines. GnRHa could not be commenced immediately if pre-pubertal (10/61), having very low bone mineral density (3/61) or low body mass index (BMI) (2/61). All who began GnRHa achieved full gonadatropin suppression. No young people withdrew from GnRHa treatment in the first 2 years. Many GPs were unwilling to prescribe GnRHa (56.0%; n = 28/50) therefore local hospitals (8.0%; n = 4) or the tertiary centre (36.0%; n = 18) issued prescriptions. Conclusion: Early medical intervention in GD with GnRH suppression of puberty is effective and well–tolerated. Assessment of growth, bone health and psychological outcomes will be important to assess the medium-and long-term safety and effectiveness of early intervention for GD.